PERSEPSI WAJIB PAJAK PADA PROGRAM TAX AMNESTY UNTUK MENINGKATKAN PENERIMAAN PAJAK - Fatmala, Nenin Dewi; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTIn order to maximize the tax, government conducts reformation by implementing policies for breakthroughswhich is driven by the reducing possibility to hide the treasure outside the territory of the Republic of Indonesia.One of the tax reformations is the current government policies about the Tax Amnesty program. This research ismeant to give the meaning on tax amnesty program as the facility of the taxpayers to carry out their opportunityin terms of tax amnesty for the purpose of the enhancement of the state revenue of the Republic Indonesia inaccordance. The research method is qualitative method which has been done by using data interpretation. Thedata has been done by using the primary. The result of the research shows that the implementation of taxamnesty will be successful if it has been run in such a way and followed by the total reformation of taxadministration system in terms of objectives through the tax amnesty will be able to increase the tax base. If thetax amnesty program has been planned in the long term and managed properly, the State will receive theenhancement of tax revenue in a short time.Keywords: tax amnesty, interpretation, tax revenue